Two cases of idiopathic membranous nephropathy treated with rituximab - Jae Young Yoon; Seung Tae Han; Ajin Cho; Hye Ryoun Jang; Jung Eun Lee; Wooseong Huh; Dae Joong Kim; Ha Young Oh; Yoon-Goo Kim (The Korean Society of Nephrology, 2013)
Idiopathic membranous nephropathy is a common cause of nephrotic syndrome, and has been reported as a cause of idiopathic primary glomerulonephropathy in up to 90% of patients. However, the treatment options remain controversial. We report two cases of idiopathic membranous nephropathy that were treated with rituximab. A 54-year-old man and a 64-year old man were admitted for rituximab therapy. They had previously been treated with combinations of immunosuppressive agents including cyclophosphamide, cyclosporine, mycophenolate, and steroids. However, the patients' heavy proteinuria was not resolved. Both patients received rituximab therapy, 2 weeks apart. After several months of follow-up and a second round of rituximab treatment for each patient, their proteinuria decreased and partial remission of disease was achieved in both patients.